Multiprofessional intervention to improve adherence to medication in stroke patients: a study protocol for a randomised controlled trial (ADMED AVC study). Issue 3 (25th September 2020) - Khettar, Sophie; Jacquin Courtois, Sophie; Luaute, Jacques; Decullier, Evelyne; Bin, Sylvie; Dupuis, Marine; Derex, Laurent; Mechtouff, Laura; Nighoghossian, Norbert; Dussart, Claude; Rode, Gilles; Janoly-Dumenil, Audrey
Abstract : Introduction: Adherence to secondary preventive medications is often suboptimal in patients with stroke, exposing them to an increased risk of recurrent cerebral and/or cardiovascular events. Effective actions in the long term to improve adherence to medication are needed. The study will evaluate the efficacy of a collaborative multiprofessional patient-centred intervention conducted by a pharmacist on adherence to secondary preventive medication in stroke survivors. Methods and analysis: This is a multicentre cluster-randomised controlled trial. Two groups of 91 patients (intervention vs standard care) will be recruited. The clinical pharmacist intervention targeting secondary preventive medication will consist of three parts over 1 year: (1) an individual semi-structured interview at hospital discharge; (2) follow-up telephone interviews at 3, 6 and 9 months after discharge; and (3) a final individual semi-structured interview 1 year after discharge. Information on patient follow-up will be shared with the general practitioner and the community pharmacist by sending a report of each interview. The primary outcome is adherence to medication during the 12 months after hospital discharge, assessed using a composite endpoint: the medication possession ratio associated with a self-administered questionnaire. Ethics and dissemination: The local ethics committee, the national committee for use of personal data in medical research and the national data protection agency approved the study. The sponsor has no role in study design; collection, analysis and interpretation of data; or report writing. Discussion: This pharmacist-led educational programme has the potential to significantly improve adherence to medication in stroke survivors which could lead to a decrease in recurrent cerebral and/or cardiovascular events. Trial registration number: NCT02611440